Pertanggungjawaban Perusahaan Pertambangan Atas Tindak Pidana di Bidang Lingkungan di Kabupaten Bombana - Saraswathi, Debby Cahya Ainun; Bima, Muhammad Rinaldy; Salle, Salle (Innovative: Journal Of Social Science Research, 2025)
Abstract This research aims to analyze the enforcement of environmental law against mining companies that cause environmental damage and to formulate an ideal model for equitable dispute resolution for affected communities. The study is driven by the occurrence of several environmental violations in Bombana Regency, notably by companies such as PT. Tonia Mitra Sejahtera, PT. Timah Investasi Mineral, and PT. Narayana Lambale Selaras. The research employs an empirical juridical method with normative and sociological approaches. Data were collected through literature study, interviews with key stakeholders, and documentation of legal cases. The data were analyzed qualitatively to describe the effectiveness of criminal law enforcement against corporations responsible for environmental harm. Findings indicate that law enforcement in these cases has largely relied on administrative sanctions and mediation, which have proven insufficient in restoring environmental and community losses. Despite the legal basis of strict liability under environmental law, criminal sanctions against corporations are rarely applied. Thus, this study proposes a restorative justice approach as a more effective solution for achieving environmental restoration and social justice. The conclusion suggests that traditional enforcement methods fail to provide deterrence and fair outcomes. Implementing restorative justice through restorative conferencing involving corporations, communities, and law enforcement can serve as an effective resolution model. Recommendation: Law enforcement authorities should strengthen the application of criminal sanctions against corporate offenders and incorporate restorative justice principles to ensure ecological sustainability and protect the rights of affected communities.